US-Mexico border as a paradigm of post-NAFTA Mexico - Barrera Herrera, Eduardo (Univ. of Massachusetts AmherstUS, 1993)
Discusses previous studies on the Mexico-US border. Questions the supposed benefits which are expected to accrue from industralization of the Mexican border.